Determination of Learning Achievement Approach School Environment and Learning Motivation in Vocational High School - Masluh Masluh; Taufiq Rahmat (UIN Sunan Gunung Djati Bandung, 2022)
The main problem in this study is the decline in student achievement, which according to the researcher's observations, the school environment and student motivation both have an impact. Based on these views and thoughts, the researcher desires to do more study the impact of the school environment and learning motivation on student accomplishment, focusing on Accounting and Institutional Finance. This study's questionnaire was 156 respondents. The descriptive and verification approaches with a quantitative approach were conducted for data analysis. Path analysis is the analytical technique used, and it is used to showcase a relationship that reveals how much effect an indicated variable has, either directly or indirectly, on many other variables. The results of this research show that partially and simultaneously, Student achievement in Accounting and Institutional Finance is favorably and strongly influenced by the school environment and learning motivation. The school environment and learning motivation variables both have an impact on student performance. This research only focuses on one vocational school and includes the school environment and motivation in measuring student achievement; many other variables have not been studied.